An analysis of the Thai Government budget - Krisada Nutalaya; Tang, John C.S.; Gupta, Joyti; Igel, Barbara; Staff Support (Bangkok : Asian Institute of Technology, 1998)
The important mechanisms that government used in control the behavior of an economy are through fiscal and monetary policies. Due to economic slow down and flotation of the baht, it strongly effected the government budget and official reserve. Eventually, the government had to request the aid from International Monetary Fund (IMF), but the government has to follow the criteria set by IMF, especially in maintaining budget surplus 1 per cent of GDP and in setting interest rate at the rate of 15-20 per cent. The high interest rate and the pressure of increasing more capital of the financial institution and bank by the Bank of Thailand made the business more difficult to make profit. Collapse of many business and a large number of unemployment were the result. For the government, the budget was cut three times from 982,000 million baht to 800,000 million baht. The cut down on spending, the government tried not to jeopardize the education, public health, people's welfare and public infrastructure programs. In addition, the government postponed the unnecessary projects and invited the private company to participate more in massive projects. However, the government could not maintain the budget surplus of 1 per cent of GDP, and the government needed to collect 100-120 million baht more tax. The economic situation seemed to be more severe than IMF and Thai government expected then, in the mid of January, IMF sent the officers to review the economic situation in Thailand and revised the third letter of intent before releasing the new package to Thailand. In the third letter of intent, the IMF relaxed the budget surplus 1 per cent of GDP to allow the budget deficit of 2 per cent of GDP. However, the government had to increase the benzene tax 1 baht per liter and to increase the excise ~ax in order to maintain enough official reserve from which the short term debt amounts to 40 million baht and the problem of the issuing virtually unlimited lines of credit through the Financial Institutions Development Fund (FIDF) must be resolved. These caused the government to fall into difficulty situation .. In addition, the government could inject upto 150 billion baht to the economic system in order to solve the liquidity problem. In order to raise more revenues to solve this financial crisis. The government should find the way to prevent the tax dodgers and tax haven, which the government loses the revenue amount to 100 billion baht each year, by improving, strengthening the law and increasing the human resource for monitoring and preventing the tax evasion. If it is successful, in the following year, the budget surplus is not difficult to achieve and it will increase the stability of the economy, prevent the increase of inflation and also restore the confidence of the investors .
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1998
Keywords: Budget -- Thailand